Pembelajaran Piano Penyandang Autisme Klasik di Modern Kawai Music School Yogyakarta: Sebuah Survey Model Pembelajaran - Khalsum, Ummy; Sitorus, Eritha Rohana; Martopo, Hari; Indrawan, Andre (Journal of Music Science, Technology, and Industry, 2021)
Purpose: This study aims to determine the development of the piano learning process and investigate whether using music will improve the skills and responses of people with autism. Research methods: This study uses qualitative methods with the subject of autism children's research, and the object of the study is piano learning. Data collection techniques utilise observation, interview and documentation. Results and discussion: The result of this study is the implementation of the weekly piano learning process for one semester with a duration of 45 minutes per meeting every afternoon. Autistic students' learning materials was the same as for regular students that included theoretical and practical materials. Implication: The obstacles faced in the learning process were a less conducive atmosphere, limited duration, and unfocused students. The LMFG approach could resolve constraints by practising it gradually and repeatedly.